Pollen morphology of Malpighiaceae from Brazilian forest fragments - Belonsi, Talita Kely [UNESP]; Gasparino, Eduardo Custódio [UNESP] (Springer Nature, 2015)
The pollen morphology of 12 Brazilian native species of Malpighiaceae from forest fragments was investigated in search to expand the morphological knowledge of the species analyzed thus contributing to its palynology, taxonomy, and conservation. The pollen grains were acetolysed, measured, photographed using light microscopy and scanning electron microscopy, and described qualitatively. The quantitative data were analyzed by descriptive statistics and multivariate statistics. The pollen grains are monads, apolar or isopolar, small to large, with circular to quadrangular amb, oblate-spheroidal to prolate-spheroidal, tricolporate with long colpi and lalongate endoaperture or 6–(7–8)-porate with or without colpoids and aspides, psilate-rugulate, rugulate or microreticulate exine, sexine thicker than nexine in most species. The results of this study point to differences in the morphology of the pollen grains in the analyzed species, which indicates Malpighiaceae as a eurypalynous family; this fact was also confirmed by quantitative data and the multivariate analysis. These data reinforce the importance of pollen morphology for identification and distinction of genus and species of the family.
Keywords: Brazil; Eurypalynous; Palynotaxonomy; Pollen grains